KEDISIPLINAN DAN KETERAMPILAN MENGAJAR GURU GUNA MEMPROTEKSI AKHLAK KARIMAH PESERTA DIDIK DI MASA PANDEMI COVID-19 - juhaeriah juhaeriah (QATHRUNÂ, 2022)
The formation of discipline and skills in the school environment from an educator will of course also have an effect on behaving and complying with all the rules that exist at school, because discipline and skills are already embedded in students to always obey and obey the rules in the school environment and seeing an educator then will protect the morals of karimah in students. The objectives of this study are: 1) To determine the discipline and skills of teachers; 2) To know the lesson plan; 3) To find out the teacher's efforts to protect the students' moral character; 4) To find out the factors that hinder the teacher's efforts to protect the morals of students. This study uses a qualitative method. The object of the research was determined by four informants from the Madrasah Ibtidaiyyah Nurul Amin, Gandaria Village, Tangerang Regency. Data was collected through observation and direct interviews with informants. Based on the research, it can be concluded that 1) The discipline and skills of teachers at Madrasah Ibtidayyah Nurul Amin, Gandaria Village, Tangerang Regency during the Covid-19 pandemic was carried out by exemplifying students with good morals, providing learning methods that were not boring and paying attention to students so that they are more active in learning even in a pandemic condition; 2) Learning planning is generally carried out with an approach to inculcating the character of karimah students into a situational approach or according to the situation of students; 3) The teacher's efforts to protect the good character of students are carried out by preparing themselves by reading story books so that the next day students will pay attention and students can receive lessons well; 4) Factors that hinder teachers' efforts to protect the morals of students include limited supervision from the madrasa, lack of awareness of students, environmental and social influences.